Artistic originality of M. V. Kratohvíl ̓s novels «Master Jan» and «Torch» - Vostrykava, Alena U. (Journal of the Belarusian State University. Philology, 2019)
The article analyzes the artistic originality of the Czech writer’s novels of the second half of the XX century, M. V. Kratohvíl «Master Jan» and «Torch». M. V. Kratohvíl is a prominent representative of the genre of the historical novel. In these works, he refers to the central image of Czech history, the image of Jan Hus. Characterized by the structure and composition of parts novels. It is evidence of a difference in interpretation of the image in these novels. Characterized by the structure and composition of parts novels. Provided depth and psychological study of all the images in the «Torch» and the black-and-white palette with the picture images in the novel «Master Jan». We consider the different role of the people in the novels. So, in the «Torch» actors are representatives of the higher social strata. In «Master Jan» appear images of people from the people, that is to follow the traditions of the Czech historical novel of the nineteenth century, in particular, appeal to the traditions of the creator historical genre in Czech literature Alois Jirásek. It concludes that the novel «Master Jan» more in line with the model of the Czech novel of the 1950s, and the «Torch» novel goes beyond the poetics and aesthetics of the time.